Transplantation of umbilical cord blood-derived mesenchymal stem cells as therapy for adriamycin induced-cardiomyopathy. Issue 4 (1st April 2022) - Zhang, Jingyue; Zhang, Shiheng; Yang, Yueming; Liu, Ling
ABSTRACT: Umbilical cord blood-derived mesenchymal stem cells (UCBMSCs) have been reported to possess cardioprotective effects in diseases. However, its effects on cardiomyopathy remain unclear. This study aimed to the therapeutic effects of UCBMSC transplantation on adriamycin (ADR)-induced cardiomyopathy. UCBMSCs isolated from human UCB were identified by detecting surface markers (CD29, CD90, CD34, and CD45) using flow cytometry. The effect of UCBMSCs on left ventricular end-diastolic dimension (LVEDD), left ventricular systolic end-diastolic diameter (LVESD), left ventricular ejection fraction (LVEF), and left ventricular fraction shortening (LVFS) were determined by echocardiography. Histological changes were observed by HE and Masson staining. The serum levels of collagen-I (Col-I), brain natriuretic peptide (BNP), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), creatine kinase (CK), CK-MB, interleukin (IL)-6, IL-10, and tumor necrosis factor alpha (TNF-α) were measured by corresponding kits. The protein levels of IL-6, IL-10, and TNF-α were measured by Western blotting. The isolated UCBMSCs manifested the positive expression of CD29 and CD90, and the negative expression of CD34 and CD45. UCBMSC transplantation significantly reduced LVEDD and LVESD, and increased LVEF and LVFS in ADR-induced cardiomyopathy model rats. Cardiac injury and high collagen deposition in model rats were alleviated by UCBMSC treatment. Moreover, UCBMSCs decreased the serum levels of Col-I, BNP, AST, LDH, CK, CK-MB, IL-6, IL-10, and TNF-α in model rats. Overall, UCBMSCs exert the therapeutic effects on ADR-induced cardiomyopathy through recovering the myocadiac function and alleviating the inflammatory response. Graphical Abstract: uf0001